Immune-Related Genes of Megalurothrips usitatus (Bagrall) Against Beauveria brongniartii and Akanthomyces attenuatus Identified Using RNA Sequencing - Chen, Yueyin; Yang, Bo; Li, Zhaoyang; Yue, Yang; Tian, Qingheng; Chen, Weiyi; Ali, Shaukat; Wu, Jianhui (Frontiers in Physiology, 2021)
Megalurothrips usitatus (Bagrall) is an important pest of legume across the world, causing great economic loss every year. Beauveria brongniartii and Akanthomyces attenuatus have shown considerable pathogencity against M. usitatus during our previous studies. This study calculated the LC50 and LC25 of B. brongniartii isolate SB010 against M. usitatus were 8.38×105 conidia ml-1 and 1.73×105 conidia ml-1 respectively, whereas the LC50 and LC25 of A. attenuatus isolate SCAUDCL-53 against M. usitatus were 4.37×105 conidia ml-1 and 2.97×104 conidia ml-1 respectively. This study reports the transcriptome based explanation of stress responses of M. usitatus following B. brongniartii and A. attenuatus application. Analysis of the transcriptomic data revealed the expression of 254, 207, 195, and 234 immunity-related unigenes by M. usitatus in response to B. brongniartii LC50 (SB1), B. brongniartii LC25 (SB2), A. attenuatus LC50 (V1) and A. attenuatus LC25 (V2), respectively. The biological functions and metabolic pathways analysis of unigenes showed that these genes were mainly related to pattern recognition receptors, information transduction factors and reaction factors, including scavenger receptor, cytochrome B5, cuticle protein, lysozyme, serine protease.